To label or not to label: balancing the risks, benefits and costs of mandatory labelling of GM food in Africa - Oh, Jessica; Ezezika, Obidimma C (BioMed Central, 2014)
There seems to be growing controversy among interest groups worldwide about whether genetically modified (GM) foods need to be labelled. There are also growing concerns, particularly among civil society groups, about the potential danger of GM foods, for which labels are being demanded. Particularly in Africa, the issue of labelling GM foods requires attention due to the rapid growth of agricultural biotechnology initiatives. Using Kenya as a case study, and based on interviews with key agricultural stakeholders and a review of the literature, we present five points to consider in discussions on how the need for mandatory GM labelling should be assessed. This framework encompasses, and is underpinned by, important considerations about ethics, consumer autonomy, costs, stigmatization, feasibility and food security as they pertain to agricultural biotechnology.
Keywords: agricultural biotechnology; genetically modified food; labelling; mandatory; Africa; Kenya